Experimental and numerical investigation of a microchannel heat sink (MCHS) with micro-scale ribs and grooves for chip cooling. (25th June 2015) - Wang, Guilian; Niu, Di; Xie, Fuqiang; Wang, Yan; Zhao, Xiaolin; Ding, Guifu
Abstract: This paper presents a microchannel heat sink (MCHS) with micro-scale ribs and grooves for chip cooling. The micro-scale ribs and grooves were both fabricated on the heated wall of the MCHS by different surface-micromachining micro-electro-mechanical system (MEMS) processes to improve the heat transfer rate. The cooling effectiveness of rib-grooved microchannels is compared with conventional smooth rectangular microchannel through experimental and numerical approaches for the Reynolds number ranged from 100 to 1000. The results indicate that the Nusselt number of rib-grooved microchannels can be 1.11–1.55 times that of smooth microchannel. Meanwhile, the utilizing of micro-scale ribs and grooves leads to high pressure drop penalty. For the rib-grooved microchannels with relative rib heights of 0.6, 0.73 and 0.85, the apparent friction factor is more than 0.38 times, 2.16 times, 4.09 times above the smooth microchannel, respectively. Graphical abstract: Highlights: The integrated manufacturing of ribs and grooves was accomplished in a MCHS by MEMS processes. The formed micro-scale ribs and grooves can increase the Nusselt number up to 1.55 times. The friction factor of rib-grooved microchannels is higher than that of smooth microchannel.